Photo of the sports club of St. Anthony - Mumbai Archive Project (Jio Institute, 2024)
Currently, the Club of St. Anthony has over 4,000 members. The glory days of the club are preserved in old photos and trophies displayed in cabinets. Kudds have strong ties with football, the most popular sport in Goa. This photo of the sports club of St. Anthony was taken in a Mumbai studio after they won a football tournament.